High-Performance Handball Player’s Time-Motion Analysis by Playing Positions - Manchado, Carmen (Int J Environ Res Public Health, 2020)
The purpose of this study was to analyze the on-court demands of handball players during the European Handball Federation Champions League Final Four (VELUX EHF FINAL4) 2019 to define time–motion characteristics (played time; covered distances) both in offense and defense. Furthermore; we aimed to define position-specific demands and differences among them. Forty players from three teams were analyzed during the tournament using a local positioning system (LPS) for the first time in top handball. Players covered similar distances both in offense (1388.28 ± 2627.08 m), and in defense (1305.47 ± 5059.64 m) and remained on court for a similar average time (15.69 ± 8.02 min and 15.40 ± 8.94 min respectively). When locomotion activities were normalized according to the time they spent on court; significant differences were found for defense compared to offense in walking (+20%; p < 0.000; Cohen’s effect size (ES) = 1.01) and jogging (−29.6%; p = 0.000; ES = 0.90), as well as a tendency for high-intensity running (+ 25.2%; p = 0.077; ES = 0.31). Per playing position; center and left back (CB = 94.86 ± 10.98 m·min(−1); LB = 96.55 ± 24.65 m·min(−1)) showed the highest running pace in offense and mid-left; front center defender and outside right for the defense (ML = 90.38 ± 30.16 m·min(−1); FCD = 87.04 ± 14.94 m·min(−1); OR = 89.64 ± 34.93 m·min(−1)). In conclusion; profile differences existed among players’ position activity; both in offense and defense; which should be taken into account when designing specific physical training programs